STRATEGI PEMANFAATAN MUSEUM SEBAGAI MEDIA PEMBELAJARAN PADA MATERI ZAMAN PRASEJARAH - Ahmad, Tsabit Azinar (Paramita: Historical Studies Journal, 2010)
Efforts of understanding of prehistoric material having the main obstacle, namely the long stretch of time between prehistoric times to the present.ÃÂ Therefore, it is necessary to solve how to increase student understanding of prehistoric material. This problem is the main subject of this research.ÃÂ This study aims to reveal how the museum can be used as instructional media of prehistoric times, so hopefully be able to improve student understanding of prehistoric times.ÃÂ One of the efforts to increase student understanding of prehistoric material can be done by using the museum as a medium of learning.ÃÂ This is due to the fact that museum offers media complexity which is very helpful for students in getting historical information.ÃÂ Utilization of the museum as a medium of learning history, in addition to providing recreational aspects for students, is also able to provide visualization, interpretation, and generalization about an historical event.ÃÂ Therefore, as an effort to improve student understanding of prehistoric material, it is necessary to optimize the use of instructional media in the form of museums. ÃÂ  Keywords: Museums, Media of Learning, Prehistoric Period Upaya pemahamanÃÂ  materi zaman prasejarah mengalamiÃÂ  kendala utama, yaitu rentangan waktu yang panjang antara zaman prasejarah dengan masa sekarang. Oleh karena itu, diperlukan adanya penyelesaian bagaimana upaya peningkatan pemahaman pelajar terhadap materi zaman prasejarah. Tulisan ini bertujuan untuk mengungkapkan bagaimana museum dapat digunakan sebagai media pembelajaran zaman prasejarah, sehingga diharapkan mampu untuk meningkatkan pemahaman pelajar terhadap zaman prasejarah. Salah satu upaya peningkatanÃÂ  pemahaman pelajar tentang materi zaman prasejarah dapat dilakukan dengan menggunakan museum sebagai media pembelajaran. Hal ini karena museum menawarkanÃÂ  kompleksitas media yang sangat membantu pelajar dalam memperoleh informasi kesejarahan. Pemanfaatan museum sebagai media pembelajaran sejarah, selain memberikan aspek rekreasi bagi pelajar, juga mampu memberikan visualisasi, interpretasi, dan generalisasi tentang suatu peristiwa sejarah. Oleh karena itu, sebagai upaya peningkatan pemahaman pelajar tentang materi zaman prasejarah perlu adanya optimalisasi penggunaan media pembelajaran berupaÃÂ  museum. ÃÂ  Kata kunci: Museum, Media Pembelajaran, Zaman Prasejarah ÃÂ